The requirements of professional football clubs in the success of the application of sports professionalism in Algeria - لعياضي عبد الحكيم; غضبان أحمد حمزة (sports creativity, 2025)
Abstract : Our study aimed at identifying the most important requirements for the application and success of professional sports in professional football clubs in Algeria. Our study consisted of 10 professional clubs in the first and second associations, which included 63 administrators and 31.81% In a simple random way. In our research, we used the descriptive approach because it is the most appropriate, and our research tool was in a questionnaire form adapted to the five-dimensional Likert scale. It was divided into two axes: the appropriateness of administrative aspects and the abundance of financial resources. The most important results are: - Lack of financial resources hinders the success of sports professionalism, and the total reliance on support does not cover the requirements of the professional club. - Appropriate administrative aspects of professional clubs as one of the most important requirements for the application of sports professionalism in Algeria. The researcher recommends the adoption of a clear strategy in the field of sports marketing by attracting specialized personnel, diversifying sources of funding for the professional club, and develop a long-term plan and build the foundations for the construction of self-financing professional club - Develop strategic plans for the professional club constituent system, based on precise and scientific principles according to the policies and principles set by the club and the setting of goals and implementation to achieve the results determined Résumé : Le but de notre étude est d'identifier les besoins les plus importants à respecter pour l'application et le succès du sport professionnel dans les clubs professionnels du football en Algérie, formé notre étude des 10 clubs professionnels dans le premier et le second, qui comprenait 63 administratif et Messier représentant 31,81%, et ils ont été sélectionnés de manière simple au hasard, et nous avons utilisé dans nos recherches sur l'approche descriptive, car il est le plus approprié, et notre outil de recherche a été le questionnaire air conditionné à l'échelle de cinq Likert, et a été divisé sur deux axes: les aspects administratifs appropriés, les ressources financières abondantes. - Les aspects administratifs appropriés des clubs professionnels comme l'une des exigences les plus importantes pour l'application du professionnalisme sportif en Algérie. Le chercheur recommande l'adoption d'une stratégie claire dans le domaine du marketing sportif en attirant du personnel spécialisé, en diversifiant les sources de financement pour le club professionnel, et en développant un plan à long terme et en construisant les bases d'un club professionnel autofinancé. - Développer des plans stratégiques pour le système constitutif des clubs professionnels, basés sur des principes précis et scientifiques en accord avec les politiques et les principes établis par le club et la fixation d'objectifs et de mise en œuvre pour atteindre les résultats établis